A microscopic analysis of role of conidia and chlamydospore during germination process in Fusarium udum (Indian Journal of Arid Horticulture, 2025)
This study is the report of Fusarium udum conidia, which are produced behind the active hyphal growth zone during filamentous growth. Monokaryons of F. udum have for a long time been known to constitutively produce abundant uninucleate asexual spores (conidia). These spores are sickle shaped, and because of this shape, they are called conidia. Chlamydospores are large, thick-walled spores of variable forms and with condensed cytoplasm. Filaments of F. udum produce both intercalary and terminal chlamydospores. During germination of the chlamydospore, a single germ tube displaces the spore pore cap. Similarly, a single germ tube is formed by the conidium. Nuclei within the germ tubes divide, and septa may be formed between the daughter nuclei; alternatively, the germ tubes may stay ascptate through several cycles of nuclear division. Multinucleate side branches emerge, while septum formation occurs in the older portions of the germ tubes to yield cell segments with one or only a few nuclei. This side branches contained new conidia. Fusarium udum,
Keywords: Fusarium udum; Conidia; Chlamydospore; Germination; Wilt